2022
DOI: 10.1039/d2ra02734h
|View full text |Cite
|
Sign up to set email alerts
|

Phase change composites of octadecane and gallium with expanded graphite as a carrier

Abstract: The thermophysical properties of the novel phase change composites formed by simultaneously packing octadecane and gallium with expanded graphite as carrier can be adjusted in a wide range, creating more options for related fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…It was found that the melting and solidifying temperature peaks of CPCSMs and DSC thermal properties of PCSM are consistent with the previous results. 31 However, composite PCSMs revealed broader and shorter endothermic and exothermic bands compared to PCSM. In addition, the peaks slightly shifted to the left for PCSM and its thermal temperatures were slightly reduced, which is attributed to the addition of silver, mechanically reinforcing and thermally stabilizing the synthesized materials.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the melting and solidifying temperature peaks of CPCSMs and DSC thermal properties of PCSM are consistent with the previous results. 31 However, composite PCSMs revealed broader and shorter endothermic and exothermic bands compared to PCSM. In addition, the peaks slightly shifted to the left for PCSM and its thermal temperatures were slightly reduced, which is attributed to the addition of silver, mechanically reinforcing and thermally stabilizing the synthesized materials.…”
Section: Resultsmentioning
confidence: 99%
“…Small samples of gallium have been seen to supercool to as low as −184 °C, over 200 °C below its melting point, before crystallization occurs . The degree of supercooling has been seen to depend on previous peak temperatures and can be altered with surface area enhancements or nucleating agents. , …”
Section: Discussion Of Thermophysical Propertiesmentioning
confidence: 99%
“…42 The degree of supercooling has been seen to depend on previous peak temperatures and can be altered with surface area enhancements or nucleating agents. 43,44 The integration of the porous metal foam was seen to benefit gallium's supercooling, as shown in Figure 11. Bulk gallium (∼100 mg) was observed to crystallize approximately 50−60 °C below the melting point.…”
Section: Supercooling Mitigationmentioning
confidence: 99%
“…In addition, since the microspheres will come into direct contact with the articular cartilage after being injected into the joint cavity, their biocompatibility should be taken into account. 58,59 Hemolytic assays showed that neither blank HAMA microspheres nor HLC composite microspheres significantly triggered rat erythrocyte rupture (Fig. 5F and G).…”
Section: Drug Loading and Biological Safety Evaluation Of Composite H...mentioning
confidence: 98%